Urban density and depression during COVID-19 in Seoul: Moderating effects of social participation - Junseong Park; Ja-Hoon Koo; Sungik Kang (PLoS ONE, 2026)
The COVID-19 pandemic, a global public health crisis, has had a profound and long-lasting impact on mental health worldwide. While existing studies on the pandemic have examined the relationship between urban characteristics and mental health, there remains a lack of understanding of the temporal distinctions of the pandemic, age-specific differences, and the role of social participation. This study empirically analyzed the relationship between COVID-19-related depressive symptoms and urban density characteristics, with a focus on the moderating effect of social participation by age group and pandemic phase. Using data from 25 Seoul districts in 2020 (initial phase) and 2021 (escalation phase), we measured depressive symptoms using a 10-point self-report scale. Urban density characteristics—population mobility density, residential density, and public transportation congestion—were derived from mobile phone signal data and building registries. We conducted ordinal logistic regression analyses with separate models for three age groups to examine associations between urban density, social participation, and depressive symptoms. First, the results revealed that population mobility density, residential density, and public transportation congestion were consistently positively associated with depressive symptoms across both study periods (2020 and 2021). Second, social participation significantly moderated the relationship between urban density characteristics and depressive symptoms, regardless of the pandemic phase. Third, the moderating effect of social participation on the relationship between urban density and depressive symptoms varied by age group. Specifically, these interaction effects were more pronounced among older adults. This study highlights the importance of understanding the complex relationships among urban density, social participation, and depressive symptoms during the COVID-19 pandemic.